Микропроцессорная система для автоматизации измерения магнитных свойств магнитотвердых материалов - Толмачев, Станислав Трофимович; Ложечка, С. М. (НТУ "ХПИ", 2008)
Рассматривается экспериментальная установка с микропроцессорным управлением, разработанная для измерения характеристик векторного гистерезиса магнитотвердых материалов. Приведены примеры магнитных характеристик для феррита бария 3БА.

Experimental installation with the microprocessor control is developed for measurement of vector hysteretic characteristics in hard-magnetic materials. Examples of magnetic characteristics for ferrite-barium are resulted.
Automated microprocessor system for measuring of magnetic parameters in hard-magnetic materials
Keywords: анизотропная гистерезисная среда; магнитное поле; измерительная система "Гистерезис"; векторный гистерезис; hard-magnetic materials; magnetic parameters; vector hysteretic characteristics; measurement; automated microprocessor system